Preparation and performance characterization of a novel high-performance epoxy resin modified reactive liquid asphalt. (10th December 2020) - Zhang, Zhu; Li, Jiusu; Wang, Zhengyuan; Long, Shiyu; Jiang, Shunjun; Liu, Guanlan
Highlights: Quite different liquefaction mechanism from that of traditional cold mix asphalt. Significant pollution and energy consumption reduction. Obvious enhancement of rheological performance by blending with epoxy resin. Abstract: In order to improve the mechanical, adhesion and high-temperature performance of liquid asphalt, Epoxy resin (EP) was blended to the liquid asphalt as a modifier. A novel cold mix asphalt was prepared by implementation the high-performance Epoxy resin modified Reactive Liquid Asphalt (ERLA) technology, where reactive liquid served as its main component. The produced cold mix asphalt had presented excellent rheological and mechanical properties (dynamic viscosity, plasticity, Marshall Stability, etc.), meeting or exceeding the requirements of pavement materials. The optimized composition for ideal comprehensive performance was studied by orthogonal designed experiments on the rheological and mechanical properties of ERLA. Infrared Spectroscopy (IR), Simultaneous Thermogravimetry & Differential Scanning Calorimetry (TG-DSC) and Laser scanning confocal microscopy (LSCM)) were used to characterize the functional group changes during curing reaction, and subsequently to evaluate the thermal stability of the material at high temperature and the compatibility of ERLA. Experimental results indicated the optimum composition of ERLA (by weight percent) is 15% reactive liquid, 40% epoxy resin and 45% original asphalt with curing agent, achieving a grade at PG 82-22. This ERLA has superior rheological and mechanical properties and therefore can be implemented for cold mix asphalt, leading to a more flexible and environment-friendly pavement construction.